Green Marketing: Consumer Perception and Corporate Strategy – A Review - Mukaram Tariqhabib Khan, (AG Volumes, 2025)
Green marketing, as opposed to traditional marketing, emphasizes the usage of environmentally beneficial products. The promotion of sustainable business practices and eco-friendly products in order to satisfy customer demands, adhere to legal requirements, and foster brand loyalty is known as "green marketing." This review examines emerging trends in green marketing in India, focusing on its impact on business performance, consumer preferences, and corporate strategies. It highlights how increasing environmental awareness has made sustainability a strategic priority rather than a promotional tactic. While eco-friendly practices enhance brand reputation and customer loyalty, challenges such as greenwashing, affordability, and the attitude–behavior gap remain. The study emphasizes the need for transparency, consumer education, and supportive policy frameworks to align green marketing with India’s sustainable development goals.